229k views
1 vote
Help with geometry hw

Help with geometry hw-example-1
Help with geometry hw-example-1
Help with geometry hw-example-2
User StoriKnow
by
6.1k points

1 Answer

1 vote

QUESTION 1

Let the third side of the right angle triangle with sides
x,6 be
l.

Then, from the Pythagoras Theorem;


l^2=x^2+6^2


l^2=x^2+36

Let the hypotenuse of the right angle triangle with sides 2,6 be
m.

Then;


m^2=6^2+2^2


m^2=36+4


m^2=40

Using the bigger right angle triangle,


(x+2)^2=m^2+l^2


\Rightarrow (x+2)^2=40+x^2+36


\Rightarrow x^2+2x+4=40+x^2+36

Group similar terms;


x^2-x^2+2x=40+36-4


\Rightarrow 2x=72


\Rightarrow x=36

QUESTION 2

Let the hypotenuse of the triangle with sides (x+2),4 be
k.

Then,
k^2=(x+2)^2+4^2


\Rightarrow k^2=(x+2)^2+16

Let the hypotenuse of the right triangle with sides 2,4 be
t.

Then; we have
t^2=2^2+4^2


t^2=4+16


t^2=20

We apply the Pythagoras Theorem to the bigger right angle triangle to obtain;


[(x+2)+2]^2=k^2+t^2


(x+4)^2=(x+2)^2+16+20


x^2+8x+16=x^2+4x+4+16+20


x^2-x^2+8x-4x=4+16+20-16


4x=24


x=6

QUESTION 3

Let the hypotenuse of the triangle with sides (x+8),10 be
p.

Then,
p^2=(x+8)^2+10^2


\Rightarrow p^2=(x+8)^2+100

Let the hypotenuse of the right triangle with sides 5,10 be
q.

Then; we have
q^2=5^2+10^2


q^2=25+100


q^2=125

We apply the Pythagoras Theorem to the bigger right angle triangle to obtain;


[(x+8)+5]^2=p^2+q^2


(x+13)^2=(x+8)^2+100+125


x^2+26x+169=x^2+16x+64+225


x^2-x^2+26x-16x=64+225-169


10x=120


x=12

QUESTION 4

Let the height of the triangle be H;

Then
H^2+4^2=8^2


H^2=8^2-4^2


H^2=64-16


H^2=48

Let the hypotenuse of the triangle with sides H,x be r.

Then;


r^2=H^2+x^2

This implies that;


r^2=48+x^2

We apply Pythagoras Theorem to the bigger triangle to get;


(4+x)^2=8^2+r^2

This implies that;


(4+x)^2=8^2+x^2+48


x^2+8x+16=64+x^2+48


x^2-x^2+8x=64+48-16


8x=96


x=12

QUESTION 5

Let the height of this triangle be c.

Then;
c^2+9^2=12^2


c^2+81=144


c^2=144-81


c^2=63

Let the hypotenuse of the right triangle with sides x,c be j.

Then;


j^2=c^2+x^2


j^2=63+x^2

We apply Pythagoras Theorem to the bigger right triangle to obtain;


(x+9)^2=j^2+12^2


(x+9)^2=63+x^2+12^2


x^2+18x+81=63+x^2+144


x^2-x^2+18x=63+144-81


18x=126


x=7

QUESTION 6

Let the height be g.

Then;


g^2+3^2=x^2


g^2=x^2-9

Let the hypotenuse of the triangle with sides g,24, be b.

Then


b^2=24^2+g^2


b^2=24^2+x^2-9


b^2=576+x^2-9


b^2=x^2+567

We apply Pythagaoras Theorem to the bigger right triangle to get;


x^2+b^2=27^2

This implies that;


x^2+x^2+567=27^2


x^2+x^2+567=729


x^2+x^2=729-567


2x^2=162


x^2=81

Take the positive square root of both sides.


x=√(81)


x=9

QUESTION 7

Let the hypotenuse of the smaller right triangle be; n.

Then;


n^2=x^2+2^2


n^2=x^2+4

Let f be the hypotenuse of the right triangle with sides 2,(x+3), be f.

Then;


f^2=2^2+(x+3)^2


f^2=4+(x+3)^2

We apply Pythagoras Theorem to the bigger right triangle to get;


(2x+3)^2=f^2+n^2


(2x+3)^2=4+(x+3)^2+x^2+4


4x^2+12x+9=4+x^2+6x+9+x^2+4


4x^2-2x^2+12x-6x=4+9+4-9


2x^2+6x-8=0


x^2+3x-4=0


(x-1)(x+4)=0


x=1,x=-4

We are dealing with length.


\therefore x=1

QUESTION 8.

We apply the leg theorem to obtain;


x(x+5)=6^2


x^2+5x=36


x^2+5x-36=0


(x+9)(x-4)=0


x=-9,x=4

We discard the negative value;


\therefore x=4

QUESTION 9;

We apply the leg theorem again;


10^2=x(x+15)


100=x^2+15x


x^2+15x-100=0

Factor;


(x-5)(x+20)=0


x=5,x=-20

Discard the negative value;


x=5

QUESTION 10

According to the leg theorem;

The length of a leg of a right triangle is the geometric mean of the lengths of the hypotenuse and the portion of the hypotenuse adjacent to that leg.

We apply the leg theorem to get;


8^2=16x


64=16x


x=4 units.

QUESTION 11

See attachment

Question 12

See attachment

Help with geometry hw-example-1
Help with geometry hw-example-2
User Mani Sankar
by
6.3k points